Scalable Software Platform Architecture for the Power Distribution Protection and Analysis - Hokkanen, Aki Ville Valtteri (My University, 2020)
This thesis explores the benefits of microservice architecture over traditional monolithic application architecture and traditional environments for deploying software to the cloud or the edge. The microservice architecture consists of multiple services that serve a single purpose and all separate functions of the application are stored in their own containers. Containers are separate environments based on the Linux kernel. This thesis was done for ABB (ASEA Brown Boveri) Distribution Solutions to modernize one of their existing applications. The main goal of this thesis is to describe the transition from a monolithic application architecture to a micro-service architecture. However, during the case study, we encountered problems that prevented us from going through with the project. The most significant of these problems was the high degree of dependence of the monolithic application between different parts of the program. The end result of the project was to be a proof of concept-level software. We couldn't achieve it. We used design science as a methodology to guide us in decision-making. We chose Action Design Research (ADR) as the methodology for our work because we found it supported interactive work. This fits in very well with our situation as we were doing this research daily at the ABB’s office. Design science primarily aims at the end result, which in our case would have been to plant the old application in the new architecture. One of our most important results is that we were able to identify critical issues that need to be addressed before moving from monolithic to microservice architecture. These findings included technological debt accumulated over the years, incomplete knowledge of the legacy application, and internal system dependencies. These dependencies represent a significant challenge in re-structuring the monolith to a microarchitecture. As a fourth finding, we found that the resources available, such as time, experts and funding, must be sufficient to produce an appropriate result. As a theoretical contribution, we produced our own version of the Action Design Research Method. We combined the first two steps of the method so that while the customer organization was defining the problem, our research team provided solutions to the problem. Of these solutions, the client organization chose the one that suited them best. This process was possible because we had an open and continuing discussion with ABB's development unit.

Tämä opinnäytetyö tutkii mikropalveluarkkitehtuurin etuja verrattuna perinteiseen monoliittiseen sovellusarkkitehtuuriin ja perinteisiin ympäristöihin. Mikropalveluarkkitehtuuri koostuu useista palveluista, jotka palvelevat kukin yhtä tarkoitusta ja sovelluksen kaikki erilliset toiminnot ovat omissa säilöissään, joita kutsutaan konteiksi. Kontit perustuvat Linux-ytimeen. Tämä opinnäytetyö tehtiin ABB (ASEA Brown Boveri) Distribution Solutions -yritykselle yhden nykyisen sovelluksen nykyaikaistamiseksi. Tämän tutkielmamme päätavoite on kuvata siirtyminen monoliittisesta sovellusarkkitehtuurista mikropalveluarkkitehtuuriin. Törmäsimme työn aikana kuitenkin ongelmiin, jotka estivät työn läpimenon. Näistä ongelmista merkittävin oli monoliittisen sovelluksen korkea riippuvuuden aste eri ohjelman osien välillä. Projektin lopputuloksen oli tarkoitus olla todiste konseptitason ohjelmistosta. Sitä emme pystyneet toteuttamaan. Käytimme toimintamallitutkimusta metodologiana ohjaamaan meitä päätöksenteossa. Valitsimme toimintamallitutkimuksen työmme metodologiaksi, koska huomasimme sen tukevan interaktiivista työskentelyä. Tämä sopi meidän tilanteeseemme erittäin hyvin, sillä olimme päivittäin ABB:n toimistolla tekemässä tätä tutkimusta. Toimintamallitutkimus tähtää ensisijaisesti lopputulokseen, joka meidän tapauksessamme olisi ollut vanhan sovelluksen istutus uuteen arkkitehtuuriin. Yksi tärkeimmistä tuloksistamme on, että onnistuimme määrittelemään kriittiset kysymykset, joihin on puututtava ennen siirtymistä monoliittisesta arkkitehtuurista mikropalveluarkkitehtuuriin. Näitä löydöksiä olivat vuosien aikana kertynyt teknologinen velka, epätäydellinen tieto vanhasta sovelluksesta sekä järjestelmän sisäiset riippuvuudet. Nämä riippuvuudet muodostavat merkittävän haasteen monoliitin uudelleen jäsentämisessä mikroarkkitehtuurin mukaiseksi. Neljäntenä löydöksenä huomasimme, että käytettävissä olevia resursseja, kuten aika, asiantuntijat ja rahoitus, on oltava riittävästi tarkoituksenmukaisen tuloksen saavuttamiseksi. Teoreettisena kontribuutiona tuotimme oman versiomme Action Design Research -menetelmään. Yhdistimme menetelmän kaksi ensimmäistä vaihetta siten, että samalla, kun asiakasorganisaatio määritteli ongelmaa, tutkimusryhmämme tarjosi ongelmiin ratkaisuja. Näistä ratkaisuista asiakasorganisaatio valitsi heille sopivimman. Tämä prosessi oli mahdollinen, koska kävimme avointa jatkuvaa keskustelua ABB:n kehitysyksikön kanssa.
Keywords: fi=Ohjelmistotekniikka|en=Software Engineering|; fi=Tietotekniikan koulutusohjelma (DI)|en=Degree Programme in Information Technology|